A City in Blue and Green The Singapore Story - Rowe, Peter G.; Hee, Limin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This open access book highlights Singapore$1 (Bs development into a city in which water and greenery, along with associated environmental, technical, social and political aspects have been harnessed and cultivated into a liveable sustainable way of life. It is also a story about a unique and thoroughgoing approach to large-scale and potentially transferable water sustainability, within largely urbanized circumstances, which can be achieved, along with complementary roles of environmental conservation, ecology, public open-space management and the greening of buildings, together with infrastructural improvements.s
Introduction -- Early Days -- Visions of Clean and Green -- Water Resources and Independence -- Gardens, Parks and Green Reserves -- Ways Forward -- Appendices -- Bibliography -- Index.
Keywords: Sustainability; Water; Hydrology; Sociology, Urban; Construction industry -- Management; Human geography; Economic geography; Sustainability; Water; Urban Sociology; Construction Management; Human Geography; Economic Geography